2022
DOI: 10.1007/s00268-022-06647-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Mortality in Emphysematous Pyelonephritis Patients: A Meta‐Analysis

Abstract: Background Emphysematous pyelonephritis (EP) is a severe necrotizing infection of the renal parenchyma which is associated with significant case mortality. We sought to identify the incidence and predictive risk factors associated with EP mortality. Methods Two electronic databases, PubMed and Web of Science, were searched from their inception until June 06, 2021 for relevant articles. Two independent teams reviewed abstracts and extracted data from the selected manuscripts. A meta-analysis has been reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 92 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…A recent meta-analysis found that the mortality rate among patients with EPN disease was 13%, with a significantly decreasing trend in mortality rates from 1985 to 2020 (5). EPN was first defined by Schultz and Klorfein (6), and they opposed open surgical drainage of multiple cortical abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that the mortality rate among patients with EPN disease was 13%, with a significantly decreasing trend in mortality rates from 1985 to 2020 (5). EPN was first defined by Schultz and Klorfein (6), and they opposed open surgical drainage of multiple cortical abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Emphysematous pyelonephritis (EP) is an uncommon condition involving acute severe necrotising infection in the renal parenchyma, collecting system and perinephric tissue [ 1 ]. Mortality rates can reach as high as 13% [ 2 ]. The risk factors for mortality include old age (≥65 years), being male, abnormal kidney function, thrombocytopaenia, disseminated intravascular coagulation, shock, disturbed consciousness levels, immunosuppression, hypoalbuminaemia and Huang–Tseng classification III–IV [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for mortality include old age (≥65 years), being male, abnormal kidney function, thrombocytopaenia, disseminated intravascular coagulation, shock, disturbed consciousness levels, immunosuppression, hypoalbuminaemia and Huang–Tseng classification III–IV [ 2 , 3 ]. EP predominantly occurs in patients with diabetes mellitus and urinary tract infections [ 2 ]. Escherichia coli and Klebsiella pneumoniae are among the most common causative pathogens that may lead to EP [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with sepsis were more likely to die but having diabetes did not appear to worsen prognosis. 7…”
mentioning
confidence: 99%